Enhanced DV-Hop Algorithm for Energy Efficiency and Network Quality in Wireless Sensor Networks - Hari, Nirwana Haidar; Sholihul Hadi, Mokh.; Sujito (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
Wireless Sensor Networks (WSN) are wireless networks with many sensor nodes covering a relatively large area. One of the weaknesses of WSN is the use of relatively high energy consumption, which affects the quality of network services. Although the WSN network routing using the DV-Hop algorithm is widely used because of its simplicity, improvements need to be made to improve energy efficiency so that the network lifetime is more optimal. This article proposes an enhanced DV-Hop algorithm compared to other algorithms to improve network energy efficiency and quality of service. There are three approaches to improving the DV-Hop algorithm. First, the selection of the CH node is based on the distance to the Base Station so that the selected CH node does not have a long distance from the base station. Second, the selection of CH nodes must have a number of neighbouring nodes above the average of other sensor nodes. Finally, each selected CH node calculates the minimum distance to the previously selected CH node to ensure that the selected CH nodes are not adjacent to each other. The proposed approach obtains better total data packets sent to the base station, energy efficiency, and network age using Matlab simulation software by comparing the enhanced DV-Hop algorithm with the original DV-Hop algorithm and three other routing algorithms.